Corporate Strategy and Executive Action: Transition Stages and Linkage Dimensions - Camillus, John C. (Academy of Management Review, 1981)
The metamorphosis of corporate strategy into operating decisions and actions has been analyzed in the policy, planning, and control literature. In this article, I integrate these perspectives into a framework that defines the stages in the transition from strategy to action as (1) business strategy, (2) action planning, (3) budgeting, and (4) executive action, for the single-business organization. For the multibusiness organization, there is an additional stage, corporate strategy, which precedes the other four. These transition stages are linked by structure, process, and content.